Scaling of characteristic frequencies of organic electronic ratchets - Roeling, Erik M.; Germs, Wijnand Chr.; Smalbrugge, Barry; Geluk, Erik Jan; Vries, Tjibbe de; Janssen, René A. J.; Kemerink, Martijn (Physical review. B, Condensed matter and materials physics, 2012)
The scaling of the characteristic frequencies of electronic ratchets operating in a flashing mode is investigated by measurements and numerical simulations. The ratchets are based on organic field effect transistors operated in accumulation mode. Oscillating potentials applied to asymmetrically spaced interdigitated finger electrodes embedded in the gate dielectric create a time-dependent, spatially asymmetric perturbation of the transistor channel potential. As a result, a net dc current can flow between source and drain despite zero source-drain bias. The frequency at current maximum is linearly dependent on the charge carrier density and the charge carrier mobility and inversely proportional to the squared length of the ratchet period, which can be related to the RC time of one asymmetric unit. Counterintuitively, it is independent of driving amplitude. Furthermore, the frequency at current maximum depends on the asymmetry of the ratchet potential, whereas the frequency of maximum charge pumping efficiency does not.
Gesehen am 09.12.2019